3, 4-dihydroxystyrene polymer, preparation thereof and photoresist composition

By using 3,4-dihydroxystyrene polymer and nanotitanium dioxide graft structure, the problem of polymer molecular weight control in photoresist is solved, the resolution and etching resistance of photoresist are improved, and the efficiency is achieved. Pure photoresist preparation.

CN119463004AActive Publication Date: 2025-02-18MICROCHIP NEW MATERIALS (HUZHOU) CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202510054172.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-02-18
Estimated Expiration
2045-01-14

AI Technical Summary

Technical Problem

Existing photoresist technology is difficult to effectively control the molecular weight of polymers, resulting in reduced material purity, low resolution and insufficient etch resistance.

Method used

Using 3,4-dihydroxystyrene-based polymers and their preparation methods, the polymerization reaction is controlled to ensure the uniformity and dispersion of molecular weight by selecting suitable solvents and reaction conditions. At the same time, the hydrothermal reaction of nanotitanium dioxide and terminal carboxy polyamide amine is used to form a graft structure to improve the resolution and adhesion of the photoresist.

Benefits of technology

It realizes effective control of polymer molecular weight, improves the resolution and etching resistance of photoresist, reduces the introduction of impurities, and improves the purity and application performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463004A_ABST
    Figure CN119463004A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of photoresist, in particular to a 3, 4-dihydroxystyrene polymer, preparation thereof and a photoresist composition. The 3, 4-dihydroxy styrene polymer is prepared from the following raw materials: 3, 4-diacetoxystyrene, a styrene monomer, tert-butyl acrylate and an initiator; the mass ratio of the 3, 4-diacetoxystyrene to the styrene monomer to the tert-butyl acrylate to the initiator is (80-100): (5-20): (10-20): (5-10). The preparation method of the 3, 4-dihydroxystyrene polymer comprises the following steps: dissolving 3, 4-diacetoxystyrene, a styrene monomer, tert-butyl acrylate and an initiator in a polar organic solvent to obtain a mixed solution; preheating a polar organic solvent to 50-80 DEG C, dropwise adding the mixed solution into the preheated organic solvent, and carrying out a constant-temperature reflux reaction at 50-80 DEG C for 2-30 h to obtain an emulsion; and decanting the emulsion, hydrolyzing, filtering, washing and drying.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photoresists, in particular to 3,4-dihydroxystyrene polymers and preparation methods thereof and photoresist compositions. Background Art

[0002] Photolithography technology is an important means of producing micro-nano-sized products in the semiconductor industry. Photoresist, as the core basic material of the photolithography process, is the basis of graphic transfer.

[0003] Photoresist, also known as photoresist, refers to a thin film material that changes its solubility when exposed to ultraviolet light, electron beam, ion beam, X-ray, etc. Photoresist is a key material for the manufacture of advanced integrated circuits. It is currently widely used in the fields of microelectronics manufacturing such as discrete devices, LEDs, integrated circuits, TFT-LCDs, etc., and has a profound impact on major fields such as information engineering, energy and environmental protection, and national defense, and plays a very important role in the development of high-tech industries and the national economy.

[0004] Photoresist is usually composed of film-forming materials, photosensitizers, solvents and other additives. Through exposure, development, etching, film removal and other processes, the pattern on the mask is transferred to a substrate such as a silicon wafer. Among them, the film-forming materials are various types of photoresist resins. In the actual polymerization process, there are many factors that affect the molecular weight of the photoresist resin polymer. Generally, the main factors affecting the molecular weight of the polymer are: polymerization reaction temperature, monomer / catalyst ratio, co-catalyst dosage, molecular weight regulator, etc. For the regulation of the molecular weight of the resin polymer, the molecular weight of the polymer is usually adjusted by changing the dosage of the initiator or chain transfer agent. With the increase of initiators or chain transfer agents, although the molecular weight is controlled, more impurities are also introduced, which not only affects the purity of the resin, but also causes the photoresist to be contaminated, resulting in material defects. At the same time, after the traditional photoresist is exposed, the acid diffusion problem of the gel sample is serious, the edge is rough, and the resolution is low.

[0005] Therefore, how to obtain a simple and effective method for controlling the molecular weight of the polymer without introducing other impurities, and to improve the resolution of the photoresist and enhance the anti-etching performance has become a technical problem that needs to be solved urgently. Summary of the invention

[0006] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a 3,4-dihydroxystyrene polymer and a preparation method thereof, and a photoresist composition and a preparation method thereof.

[0007] A 3,4-dihydroxystyrene polymer, whose raw materials include: 3,4-diacetoxystyrene, styrene monomer, tert-butyl acrylate, and initiator; the mass ratio of 3,4-diacetoxystyrene, styrene monomer, tert-butyl acrylate, and initiator is 80-100: 5-20: 10-20: 5-10.

[0008] Its structural formula is as follows: .

[0009] Preferably, the initiator is azobisisoheptanitrile or / and dimethyl azobisisobutyrate.

[0010] The preparation method of the above 3,4-dihydroxystyrene polymer comprises the following steps: (1) 3,4-diacetoxystyrene, styrene monomer, and tert-butyl acrylate are uniformly mixed to obtain a monomer solution; (2) preheating the polar organic solvent to 50-80° C., adding the monomer solution and the initiator obtained in step (1) to the preheated organic solvent, and refluxing at 50-80° C. for 2-30 hours to obtain an emulsion; (3) The emulsion obtained in step (2) is purified, then hydrolyzed, filtered, washed and dried.

[0011] Preferably, the specific operation of purification is as follows: adding the emulsion obtained in step (2) to a polar organic solvent at a temperature of 30-80°C, continuing to stir for 1-10 hours after complete dissolution, then cooling to 5-15°C, and decanting the upper solution; then adding it to a non-polar organic solvent at a temperature of 30-80°C, continuing to stir for 1-10 hours after complete dissolution, then cooling to 5-15°C, and decanting the upper solution; then adding it to a polar organic solvent at a temperature of 30-80°C, continuing to stir for 1-10 hours after complete dissolution, then cooling to 5-15°C, and decanting the upper solution.

[0012] Preferably, the specific operation of hydrolysis is as follows: add the purified product to a polar organic solvent at a temperature of 30-80°C, stir after complete dissolution, add 20-28% ammonia water during stirring, and react at 30-50°C for 10-24h.

[0013] Preferably, the specific operation of washing is as follows: add the filtrate obtained by filtration into ethyl acetate, heat it to 20-30°C, add deionized water after complete dissolution, heat it to 45-55°C, stir and separate into layers, and discard the lower aqueous phase.

[0014] A photoresist composition, the raw materials of which include, by mass percentage: 10-30% of the above-mentioned 3,4-dihydroxystyrene polymer, 2-5% of nano silicon dioxide, 0.5-1% of terminal carboxyl polyamide amine, 1-2% of polyvinyl pyrrolidone, 1-3% of 3-hydroxy-1-adamantyl methacrylate, 0.2-1% of photoacid generator, 0.01-0.2% of alkaline additive, 0.01-0.15% of leveling agent, and the balance is solvent.

[0015] Preferably, the photoacid generator is at least one of diphenyliodonium trifluoromethanesulfonate, diphenyliodonium camphorsulfonate, diphenyliodonium perfluoro-1-butanesulfonate, diphenyliodonium perfluorooctanesulfonate, triphenylsulfonium trifluoromethanesulfonate, triphenylsulfonium camphorsulfonate, triphenylsulfonium perfluoro-1-butanesulfonate, and triphenylsulfonium perfluorooctanesulfonate.

[0016] Preferably, the alkaline additive is at least one of tetrabutylammonium hydroxide, tetrabutylammonium acetate, tri-n-octylamine, 2,6-diisopropylamine and diethanolamine.

[0017] Preferably, the solvent is at least one of propylene glycol methyl ether acetate, ethyl lactate, 2-heptanone, ethylene glycol monomethyl ether acetate, and cyclohexanone.

[0018] The preparation method of the above-mentioned photoresist composition comprises the following steps: S1. Add nano-silicon dioxide, carboxyl-terminated polyamidoamine and polyvinyl pyrrolidone to water for ultrasonic treatment for 1-2 hours, perform hydrothermal reaction at 200-230° C. for 2-6 hours, and the reaction pressure is 0.8-1 MPa. Then, the mixture is cooled to room temperature, centrifuged, washed, vacuum dried and crushed to obtain grafted titanium dioxide. S2. Add grafted titanium dioxide to water and stir evenly, add a photoacid generator thereto and ultrasonically treat for 1-2 hours, spray dry, add the above-mentioned 3,4-dihydroxystyrene polymer, 3-hydroxy-1-adamantyl methacrylate, alkaline additive, and leveling agent and mix evenly, add a solvent and mix evenly.

[0019] The method for using the above-mentioned photoresist composition is characterized in that it comprises the following steps: spin coating the above-mentioned photoresist composition on a silicon wafer, and sequentially performing pre-baking, exposure, post-baking and development to obtain a photolithographic pattern; wherein the pre-baking temperature is 70-120°C, and the exposure energy is 5-70mJ / cm 2 , post-baking temperature is 90-150℃; developing time is 30-130s.

[0020] Preferably, a tetramethylammonium hydroxide solution is used as the developer, and the mass fraction of the tetramethylammonium hydroxide solution is 2.38%.

[0021] Beneficial effects: The purpose of the present invention is to provide a film-forming material that can conveniently and effectively control the molecular weight of the polymer without introducing other impurities. The present invention can effectively promote the polymerization reaction by selecting a solvent, effectively control the molecular weight range of the resin, strictly control the introduction of metal ions during the reaction, and use electronic grade materials throughout the process, so that the product can reach a metal ion level of less than 10ppb, and the total metal ion content can reach less than 50ppb. At the same time, the polymerization conditions of the present invention are mild, the polymer molecular weight and its distribution are highly controllable, the polymer product performance is excellent, and the product application performance is good. After the laboratory feasibility reaction test of the present invention, it is introduced into industrial production on this basis.

[0022] The present invention adopts nano titanium dioxide and carboxyl-terminated polyamide amine in combination, and in the presence of polyvinyl pyrrolidone, a dendritic polyamide amine structure is grafted on the surface of titanium dioxide through a hydrothermal reaction, which not only causes the nano titanium dioxide particles to produce steric hindrance, effectively overcomes the agglomeration phenomenon, and ensures the original light absorption performance of the nano titanium dioxide, but also the grafted titanium dioxide is compounded with a photoacid generator and loaded on the photoacid generator, which can quickly transfer the light absorption energy to a photosensitizer, so that the photoresist has the characteristic of small line edge roughness during the photolithography process, and effectively improves the resolution.

[0023] Compared with a single nano titanium dioxide material, the grafted nano titanium dioxide obtained by the present invention is beneficial to reducing the surface tension of the photoresist and enhancing the wetting of the substrate. It is compounded with 3,4-dihydroxystyrene polymers and 3-hydroxy-1-adamantyl methacrylate to improve the adhesion between the photoresist film and the substrate and reduce the penetration of acid molecules. At the same time, the photoresist film has high density and improves the resolution of the photoresist. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a photo of the 3,4-dihydroxystyrene polymer obtained in Example 4.

[0025] Figure 2 This is a photograph of a solution of 3,4-dihydroxystyrene polymer obtained in Example 4 dissolved in propylene glycol methyl ether acetate.

[0026] Figure 3 is the number average molecular weight of the 3,4-dihydroxystyrene polymer obtained in Examples 1-4 ( M w ), polymer dispersibility index (PDI) comparison chart.

[0027] Figure 4 This is the gel permeation chromatogram of the 3,4-dihydroxystyrene polymer obtained in Example 4.

[0028] Figure 5 This is the infrared spectrum of the 3,4-dihydroxystyrene polymer obtained in Example 4.

[0029] Figure 6 This is the UV spectrum of the 3,4-dihydroxystyrene polymer obtained in Example 4.

[0030] Figure 7 The following is a comparison chart of the resolution and sensitivity of the photoresist compositions obtained in Example 7 and Comparative Examples 1-3 after photolithography. DETAILED DESCRIPTION

[0031] The present invention will be further explained below in conjunction with specific embodiments.

[0032] The raw materials used below are all electronic grade products.

[0033] Example 1: 1.1 Polymerization reaction: Add 40 mL of methanol to a 1000 mL three-necked flask, stir mechanically, control the reaction temperature to 68°C, and set the speed to 350 rpm. Add 90 g of 3,4-diacetoxystyrene, 25 g of styrene, and 18 g of tert-butyl acrylate to dropping funnel 1 and mix evenly; add azobisisobutyronitrile solution (8 g of azobisisobutyronitrile dissolved in 220 mL of methanol) to dropping funnel 2; control the dropping time to be 6.5 h. After the dropping is completed, a blue-glowing emulsion appears.

[0034] After the addition was completed, the temperature was controlled and the polymerization was continued for 8 hours. The product in the flask was a viscous white emulsion.

[0035] 1.2 Purification: After the above polymerization reaction is completed, add 250 mL of methanol to the flask, heat to 58°C, dissolve the crude product and stir at 350 rpm for 1.5 h. After stopping stirring, cool to 12°C and decant the upper methanol solution; repeat the above methanol decantation step twice.

[0036] Add 220 mL of n-heptane to the flask, raise the temperature to 58°C, dissolve the crude product and stir at 350 rpm for 1.5 h. Stop stirring, cool to 12°C, and decant the upper n-heptane solution; repeat the above n-heptane decantation step once.

[0037] Add 250 mL of methanol to the flask, raise the temperature to 58°C, dissolve the crude product, and stir at 350 rpm for 1.5 h. After stopping stirring, cool to 12°C and decant the upper methanol solution.

[0038] 1.3 Hydrolysis: After the above decantation, add 250 mL of methanol to the flask, heat to 58°C to dissolve the product, start stirring, and add 40 g of 28% ammonia water, and control the reaction time to 12 hours. After the reaction is completed, a brown viscous solution is formed.

[0039] 1.4 Filtration: Use 0.2μm filter membrane. The filtration speed is moderate and takes about 12 hours.

[0040] 1.5 Washing: After the above filtration, add 2kg of ethyl acetate, raise the temperature to 25°C, add 450g of deionized water after dissolution, heat to 55°C, stir for 15 minutes and stop, transfer to a separatory funnel, separate the layers, and discard the lower aqueous phase. Continue to add deionized water, repeat the above steps 5 times, and the total amount of deionized water used is 2.8kg. Finally, the ethyl acetate phase is subjected to rotary evaporation to remove most of the ethyl acetate to obtain a light brown solid.

[0041] Example 2: 2.1 Polymerization reaction: Add 35 mL of methanol to a 1000 mL three-necked flask, stir mechanically, control the reaction temperature to 66°C, and set the speed to 280 rpm. Add 78 g of 3,4-diacetoxystyrene, 20 g of styrene, and 15 g of tert-butyl acrylate to dropping funnel 1 and mix evenly; add azobisisobutyronitrile solution (6.5 g of azobisisobutyronitrile dissolved in 180 mL of methanol) to dropping funnel 2; control the dropping time to be 6.2 h. After the dropping is completed, a blue-glowing emulsion appears.

[0042] After the addition was completed, the temperature was controlled and the polymerization was continued for 7.8 hours. The product in the flask was a viscous white emulsion.

[0043] 2.2 Purification: After the above polymerization reaction is completed, add 220 mL of methanol to the flask, heat to 56°C, dissolve the crude product and stir at 280 rpm for 1.2 h. After stopping stirring, cool to 12°C and decant the upper methanol solution; repeat the above methanol decantation step twice.

[0044] Add 190 mL of n-heptane to the flask, raise the temperature to 56°C, dissolve the crude product and stir at 280 rpm for 1.5 h. Stop stirring, cool to 12°C, and decant the upper n-heptane solution; repeat the above n-heptane decantation step once.

[0045] Add 220 mL of methanol to the flask, raise the temperature to 56°C, dissolve the crude product, and stir at 280 rpm for 1.2 h. After stopping stirring, cool to 12°C and decant the upper methanol solution.

[0046] 2.3 Hydrolysis: After the above decantation, add 210 mL of methanol to the flask, heat to 57°C to dissolve the product, start stirring, and add 35 g of 28% ammonia water, and control the reaction time to 11 hours. After the reaction is completed, a brown viscous solution is formed.

[0047] 2.4 Filtration: Use 0.2μm filter membrane. The filtration speed is moderate and takes about 14 hours.

[0048] 2.5 Washing: After the above filtration, add 1.6 kg of ethyl acetate, raise the temperature to 22 ° C, add 380 g of deionized water after dissolution, heat to 48 ° C, stir for 15 minutes and stop, transfer to a separatory funnel, separate the layers, and discard the lower aqueous phase. Continue to add deionized water, repeat the above steps 5 times, and the total amount of deionized water used is 2.2 kg. Finally, the ethyl acetate phase is subjected to rotary evaporation to remove most of the ethyl acetate to obtain a light brown solid.

[0049] Example 3: 3.1 Polymerization reaction: Add 40 mL of methanol to a 1000 mL three-necked flask, stir mechanically, control the reaction temperature to 65 °C, and set the speed to 300 rpm. Add 80 g of 3,4-diacetoxystyrene, 25 g of styrene, and 20 g of tert-butyl acrylate to dropping funnel 1 and mix evenly; add azobisisobutyronitrile solution (7.5 g of azobisisobutyronitrile dissolved in 200 mL of methanol) to dropping funnel 2; control the dropping time to be 6.5 h. After the dropping is completed, a blue-glowing emulsion appears.

[0050] After the addition was completed, the temperature was controlled and the polymerization was continued for 8 hours. The product in the flask was a viscous white emulsion.

[0051] 3.2 Purification: After the above polymerization reaction is completed, add 230 mL of methanol to the flask, heat to 55°C, dissolve the crude product and stir at 300 rpm for 1 hour. After stopping stirring, cool to 10°C and decant the upper methanol solution; repeat the above methanol decantation step twice.

[0052] Add 200 mL of n-heptane to the flask, raise the temperature to 55°C, dissolve the crude product and stir at 300 rpm for 1 hour. Stop stirring, cool to 10°C, and decant the upper n-heptane solution; repeat the above n-heptane decantation step once.

[0053] Add 230 mL of methanol to the flask, raise the temperature to 55°C, dissolve the crude product, and stir at 300 rpm for 1 h. After stopping stirring, cool to 10°C and decant the upper methanol solution.

[0054] 3.3 Hydrolysis: After the above decantation, add 200 mL of methanol to the flask, heat to 55°C to dissolve the product, start stirring, and add 33 g of 28% ammonia water, and control the reaction time to 10 hours. After the reaction is completed, a brown viscous solution is formed.

[0055] 3.4 Filtration: Use 0.2μm filter membrane. The filtration speed is moderate and takes about 10 hours.

[0056] 3.5 Washing: After the above filtration, add 1.8 kg of ethyl acetate, raise the temperature to 25 ° C, add 400 g of deionized water after dissolution, heat to 50 ° C, stir for 15 minutes and stop, transfer to a separatory funnel, separate the layers, and discard the lower aqueous phase. Continue to add deionized water, repeat the above steps 5 times, and the total amount of deionized water used is 2.5 kg. Finally, the ethyl acetate phase is subjected to rotary evaporation to remove most of the ethyl acetate to obtain a light brown solid.

[0057] Example 4: 4.1 Polymerization reaction: Add 39 mL of methanol to a 1000 mL three-necked flask, stir mechanically, control the reaction temperature to 67 °C, and set the speed to 310 rpm. Add 87 g of 3,4-diacetoxystyrene, 22.5 g of styrene, and 17.2 g of tert-butyl acrylate to dropping funnel 1 and mix evenly; add azobisisobutyronitrile solution (7.6 g of azobisisobutyronitrile dissolved in 210 mL of methanol) to dropping funnel 2; control the dropping time to 6.3 h. After the addition is completed, a blue-glowing emulsion appears.

[0058] After the addition was completed, the temperature was controlled and the polymerization was continued for 7.5 hours. The product in the flask was a viscous white emulsion.

[0059] 4.2 Purification: After the above polymerization reaction is completed, add 238 mL of methanol to the flask, heat to 57°C, dissolve the crude product and stir at 310 rpm for 1 hour. After stopping stirring, cool to 11°C and decant the upper methanol solution; repeat the above methanol decantation step twice.

[0060] Add 205 mL of n-heptane to the flask, raise the temperature to 57°C, dissolve the crude product and stir at 310 rpm for 1 hour. Stop stirring, cool to 11°C, and decant the upper n-heptane solution; repeat the above n-heptane decantation step once.

[0061] Add 238 mL of methanol to the flask, raise the temperature to 57°C, dissolve the crude product, and stir at 310 rpm for 1 h. After stopping stirring, cool to 11°C and decant the upper methanol solution.

[0062] 4.3 Hydrolysis: After the above decantation, add 238 mL of methanol to the flask, heat to 57°C to dissolve the product, start stirring, and add 39.5 g of 28% ammonia water, and control the reaction time to 11 hours. After the reaction is completed, a brown viscous solution is formed.

[0063] 4.4 Filtration: Use 0.2μm filter membrane. The filtration speed is slow and takes about 24 hours.

[0064] 4.5 Washing: After the above filtration, add 1.86 kg of ethyl acetate, raise the temperature to 27 ° C, add 430 g of deionized water after dissolution, heat to 54 ° C, stir for 11 minutes and stop, transfer to a separatory funnel, separate the layers, and discard the lower aqueous phase. Continue to add deionized water, repeat the above steps 5 times, and the total amount of deionized water used is 2.58 kg. Finally, the ethyl acetate phase is subjected to rotary evaporation to remove most of the ethyl acetate to obtain a light brown solid (such as Figure 1 The light brown solid obtained in this example was dissolved in propylene glycol methyl ether acetate. Figure 2 shown.

[0065] The 3,4-dihydroxystyrene polymers obtained in Examples 1-4 were subjected to gel permeation chromatography analysis, and the results were as follows: Figure 3 The gel permeation chromatogram of the 3,4-dihydroxystyrene polymer obtained in Example 4 is shown in Figure 4 As shown, its infrared spectrum is as follows Figure 5 As shown, the UV spectrum is Figure 6 shown.

[0066] Depend on Figure 3-Figure 6 It can be seen that the number average molecular weight of the 3,4-dihydroxystyrene polymers obtained in Examples 1-4 is 18000-22000, and the polymer dispersity index is 1.48-1.52, which proves that the present invention effectively controls the molecular weight range of the polymer.

[0067] Example 5: A photoresist composition, whose raw materials include, by mass percentage: 10% of the 3,4-dihydroxystyrene polymer obtained in Example 4, 2% of P25 nano-silica, 0.5% of terminal carboxyl polyamide amine, 1% of polyvinyl pyrrolidone, 1% of 3-hydroxy-1-adamantyl methacrylate, 0.2% of triphenylsulfonium perfluoro-1-butanesulfonate, 0.01% of tri-n-octylamine, 0.01% of 3M fluorocarbon surfactant FC-4430, and the balance of propylene glycol methyl ether acetate.

[0068] The preparation method of the above-mentioned photoresist composition comprises the following steps: S1. P25 nano-silica, carboxyl-terminated polyamidoamine and polyvinyl pyrrolidone were added to water for ultrasonic treatment for 1 h, with an ultrasonic frequency of 5 kHz, and hydrothermal reaction at 200 °C for 2 h, with a reaction pressure of 0.8 MPa, cooled to room temperature, centrifuged, washed once with deionized water, vacuum dried, and crushed to obtain grafted titanium dioxide; S2. Add grafted titanium dioxide to deionized water and stir evenly, add triphenylsulfonium perfluoro-1-butanesulfonate thereto and ultrasonically treat for 1 hour at an ultrasonic frequency of 3 kHz, spray dry, add 3,4-dihydroxystyrene polymer obtained in Example 4, 3-hydroxy-1-adamantyl methacrylate, tri-n-octylamine, and 3M fluorocarbon surfactant FC-4430, mix evenly, add propylene glycol methyl ether acetate, mix evenly, and then filter through a 0.25 μm nylon membrane.

[0069] Example 6: A photoresist composition, whose raw materials include, by mass percentage: 30% of the 3,4-dihydroxystyrene polymer obtained in Example 4, 5% of P25 nano-silica, 1% of terminal carboxyl polyamide amine, 2% of polyvinyl pyrrolidone, 3% of 3-hydroxy-1-adamantyl methacrylate, 1% of triphenylsulfonium perfluoro-1-butanesulfonate, 0.2% of tri-n-octylamine, 0.15% of 3M fluorocarbon surfactant FC-4430, and the balance of propylene glycol methyl ether acetate.

[0070] The preparation method of the above-mentioned photoresist composition comprises the following steps: S1. P25 nano-silica, carboxyl-terminated polyamidoamine and polyvinyl pyrrolidone were added to water for ultrasonic treatment for 2 h, the ultrasonic frequency was 15 kHz, the hydrothermal reaction was carried out at 230 ° C for 6 h, the reaction pressure was 1 MPa, the reaction was cooled to room temperature, centrifuged, washed with deionized water for 3 times, vacuum dried, and crushed to obtain grafted titanium dioxide; S2. Add grafted titanium dioxide to deionized water and stir evenly, add triphenylsulfonium perfluoro-1-butanesulfonate thereto and ultrasonically treat for 2 hours at an ultrasonic frequency of 10 kHz, spray dry, add 3,4-dihydroxystyrene polymer obtained in Example 4, 3-hydroxy-1-adamantyl methacrylate, tri-n-octylamine, and 3M fluorocarbon surfactant FC-4430, mix evenly, add propylene glycol methyl ether acetate, mix evenly, and then filter through a 0.25 μm nylon membrane.

[0071] Example 7: A photoresist composition, whose raw materials include, by mass percentage: 20% of the 3,4-dihydroxystyrene polymer obtained in Example 4, 3.5% of P25 nano-titanium dioxide, 0.8% of terminal carboxyl polyamide amine, 1.5% of polyvinyl pyrrolidone, 2% of 3-hydroxy-1-adamantyl methacrylate, 0.6% of triphenylsulfonium perfluoro-1-butanesulfonate, 0.1% of tri-n-octylamine, 0.1% of 3M fluorocarbon surfactant FC-4430, and the balance of propylene glycol methyl ether acetate.

[0072] The preparation method of the above-mentioned photoresist composition comprises the following steps: S1. P25 nano-silica, carboxyl-terminated polyamidoamine and polyvinyl pyrrolidone were added to water for ultrasonic treatment for 1.5 h, the ultrasonic frequency was 9 kHz, the hydrothermal reaction was carried out at 220°C for 4 h, the reaction pressure was 0.9 MPa, the reaction was cooled to room temperature, centrifuged, washed twice with deionized water, vacuum dried, and crushed to obtain grafted titanium dioxide; S2. Add grafted titanium dioxide to deionized water and stir evenly, add triphenylsulfonium perfluoro-1-butanesulfonate thereto, ultrasonically treat for 1.5 hours at an ultrasonic frequency of 6 kHz, spray dry, add 3,4-dihydroxystyrene polymer obtained in Example 4, 3-hydroxy-1-adamantyl methacrylate, tri-n-octylamine, and 3M fluorocarbon surfactant FC-4430, mix evenly, add propylene glycol methyl ether acetate, mix evenly, and then filter through a 0.25 μm nylon membrane.

[0073] Comparative Example 1: A photoresist composition, wherein the raw materials thereof include, by mass percentage: 22% of the 3,4-dihydroxystyrene polymer obtained in Example 4, 3.5% of P25 nano-titanium dioxide, 0.8% of terminal carboxyl polyamide amine, 1.5% of polyvinyl pyrrolidone, 0.6% of triphenylsulfonium perfluoro-1-butanesulfonate, 0.1% of tri-n-octylamine, 0.1% of 3M fluorocarbon surfactant FC-4430, and the balance of propylene glycol methyl ether acetate.

[0074] The preparation method of the above-mentioned photoresist composition comprises the following steps: S1. P25 nano-silica, carboxyl-terminated polyamidoamine and polyvinyl pyrrolidone were added to water for ultrasonic treatment for 1.5 h, the ultrasonic frequency was 9 kHz, the hydrothermal reaction was carried out at 220°C for 4 h, the reaction pressure was 0.9 MPa, the reaction was cooled to room temperature, centrifuged, washed twice with deionized water, vacuum dried, and crushed to obtain grafted titanium dioxide; S2. Add grafted titanium dioxide to deionized water and stir evenly, add triphenylsulfonium perfluoro-1-butanesulfonate thereto, ultrasonically treat for 1.5 hours at an ultrasonic frequency of 6 kHz, spray dry, add 3,4-dihydroxystyrene polymer tri-n-octylamine obtained in Example 4 and 3M fluorocarbon surfactant FC-4430, mix evenly, add propylene glycol methyl ether acetate, mix evenly, and then filter through a 0.25 μm nylon membrane.

[0075] Comparative Example 2: A photoresist composition, wherein the raw materials thereof include, by mass percentage: 20% of the 3,4-dihydroxystyrene polymer obtained in Example 4, 3.5% of P25 nano-titanium dioxide, 0.8% of terminal carboxyl polyamide amine, 1.5% of polyvinyl pyrrolidone, 2% of 3-hydroxy-1-adamantyl methacrylate, 0.6% of triphenylsulfonium perfluoro-1-butanesulfonate, 0.1% of tri-n-octylamine, 0.1% of 3M fluorocarbon surfactant FC-4430, and the balance of propylene glycol methyl ether acetate.

[0076] The preparation method of the above-mentioned photoresist composition comprises the following steps: S1. P25 nano-silica, carboxyl-terminated polyamidoamine and polyvinyl pyrrolidone were added to water for ultrasonic treatment for 1.5 h, the ultrasonic frequency was 9 kHz, the hydrothermal reaction was carried out at 220°C for 4 h, the reaction pressure was 0.9 MPa, the reaction was cooled to room temperature, centrifuged, washed twice with deionized water, vacuum dried, and crushed to obtain grafted titanium dioxide; S2. Evenly mix the grafted titanium dioxide, triphenylsulfonium perfluoro-1-butanesulfonate, the 3,4-dihydroxystyrene polymer obtained in Example 4, 3-hydroxy-1-adamantyl methacrylate, tri-n-octylamine, and 3M fluorocarbon surfactant FC-4430, add propylene glycol methyl ether acetate and mix evenly, and then filter through a 0.25 μm nylon membrane.

[0077] Comparative Example 3: A photoresist composition, wherein the raw materials thereof include, by mass percentage: 20% of the 3,4-dihydroxystyrene polymer obtained in Example 4, 3.5% of P25 nano-titanium dioxide, 0.8% of terminal carboxyl polyamide amine, 1.5% of polyvinyl pyrrolidone, 2% of 3-hydroxy-1-adamantyl methacrylate, 0.6% of triphenylsulfonium perfluoro-1-butanesulfonate, 0.1% of tri-n-octylamine, 0.1% of 3M fluorocarbon surfactant FC-4430, and the balance of propylene glycol methyl ether acetate.

[0078] The preparation method of the above-mentioned photoresist composition comprises the following steps: S1, mixing P25 nano-silicon dioxide and carboxyl-terminated polyamidoamine to obtain composite titanium dioxide; S2. Add the composite titanium dioxide to deionized water and stir evenly, add triphenylsulfonium perfluoro-1-butanesulfonate thereto, ultrasonically treat for 1.5 hours at an ultrasonic frequency of 6 kHz, spray dry, add the 3,4-dihydroxystyrene polymer obtained in Example 4, 3-hydroxy-1-adamantyl methacrylate, tri-n-octylamine, and 3M fluorocarbon surfactant FC-4430, mix evenly, add propylene glycol methyl ether acetate, mix evenly, and then filter through a 0.25 μm nylon membrane.

[0079] Photolithography was performed using the photoresist compositions obtained in Example 7 and Comparative Examples 1-3, specifically as follows: each group of photoresist compositions was spin-coated on a silicon wafer, pre-baked at 100°C for 90 seconds, then selectively exposed using a KrF exposure machine, and then post-baked at 130°C for 90 seconds. After the silicon wafer was cooled to room temperature, it was developed using a 2.38% tetramethylammonium hydroxide aqueous solution developer for 60 seconds, and finally rinsed with deionized water for 45 seconds to obtain the desired photolithography pattern.

[0080] Resolution evaluation: Observe using a scanning electron microscope to test its minimum resolution.

[0081] Sensitivity evaluation: The photosensitivity is measured using a scanning electron microscope. The sensitivity is the minimum exposure that clearly displays a pattern with a line width of 150nm (line: spacing = 1:1). The smaller the exposure value, the higher the sensitivity.

[0082] like Figure 7 As shown, the photoresist composition obtained in Example 7 exhibits extremely high resolution and sensitivity, which is better than that of Comparative Examples 1-3 (P < 0.05).

[0083] At the same time, the cross-sectional shape of the line pattern obtained at the minimum exposure in the above sensitivity test was observed using a scanning electron microscope. When the ratio of the top line width / bottom line width of the line pattern was ≥1.2, the cross-sectional shape of the line pattern was an inverted trapezoid, and the pattern quality was poor; when the ratio was within 1.1-1.2, the pattern quality was qualified; when the ratio was <1.1, the cross-sectional shape of the line pattern was a rectangle, and the pattern quality was good. The pattern quality of the photoresist compositions obtained in Example 7 and Comparative Examples 1-3 was good.

[0084] The applicant believes that: the present invention adopts nano titanium dioxide and carboxyl-terminated polyamide amine to be matched, and in the cooperation of polyvinyl pyrrolidone, the dendritic polyamide amine structure is grafted on the titanium dioxide surface through a hydrothermal reaction, which not only promotes the nano titanium dioxide particles to produce steric hindrance, effectively overcomes the agglomeration phenomenon, and ensures the original light absorption performance of nano titanium dioxide, but also the grafted titanium dioxide is compounded with a photoacid generator and loaded with the photoacid generator, which can quickly transfer the light absorption energy to the photosensitizer, so that the photoresist has the characteristics of small line edge roughness during the photolithography process, and effectively improves the resolution. At the same time, the grafted nano titanium dioxide obtained by the present invention is conducive to reducing the surface tension of the photoresist, enhancing the wetting of the substrate, and compounding with 3,4-dihydroxystyrene polymers and 3-hydroxy-1-adamantyl methacrylate can improve the adhesion between the photoresist film and the substrate, reduce the penetration of acid molecules, and at the same time, the photoresist film has high density, which improves the resolution of the photoresist.

[0085] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A 3,4-dihydroxystyrene polymer, characterized in that: The raw materials include: 3,4-diacetoxystyrene, styrene monomer, tert-butyl acrylate, initiator; The mass ratio of 3,4-diacetoxystyrene, styrene monomer, tert-butyl acrylate and initiator is 80-100:5-20:10-20:5-10.

2. The 3,4-dihydroxystyrene polymer according to claim 1, characterized in that: The initiator is azobisisoheptanitrile or / and dimethyl azobisisobutyrate.

3. A method for preparing a 3,4-dihydroxystyrene polymer as claimed in claim 1 or 2, characterized in that: The steps include: (1) 3,4-diacetoxystyrene, styrene monomer, and tert-butyl acrylate are uniformly mixed to obtain a monomer solution; (2) preheating the polar organic solvent to 50-80° C., adding the monomer solution and the initiator obtained in step (1) to the preheated organic solvent, and refluxing at 50-80° C. for 2-30 hours to obtain an emulsion; (3) The emulsion obtained in step (2) is purified, then hydrolyzed, filtered, washed and dried.

4. The method for preparing 3,4-dihydroxystyrene polymer according to claim 3, characterized in that: The specific operation of purification is as follows: add the emulsion obtained in step (2) to a polar organic solvent at a temperature of 30-80°C, continue stirring for 1-10 hours after complete dissolution, then cool to 5-15°C, and decant the upper solution; then add it to a non-polar organic solvent at a temperature of 30-80°C, continue stirring for 1-10 hours after complete dissolution, then cool to 5-15°C, and decant the upper solution; then add it to a polar organic solvent at a temperature of 30-80°C, continue stirring for 1-10 hours after complete dissolution, then cool to 5-15°C, and decant the upper solution.

5. The method for preparing 3,4-dihydroxystyrene polymer according to claim 3, characterized in that: The specific operation of hydrolysis is as follows: add the purified product to a polar organic solvent at a temperature of 30-80°C, stir after complete dissolution, add 20-28% ammonia water during stirring, and react at 30-50°C for 10-24h.

6. The method for preparing 3,4-dihydroxystyrene polymer according to claim 3, characterized in that: The specific operation of washing is as follows: add the filtrate obtained by filtration into ethyl acetate, heat it to 20-30°C, add deionized water after it is completely dissolved, heat it to 45-55°C, stir and separate the layers, and discard the lower aqueous phase.

7. A photoresist composition, characterized in that The raw materials include, by mass percentage, 10-30% of the 3,4-dihydroxystyrene polymer as claimed in claim 1 or 2, 2-5% of nano silicon dioxide, 0.5-1% of terminal carboxyl polyamide amine, 1-2% of polyvinyl pyrrolidone, 1-3% of 3-hydroxy-1-adamantyl methacrylate, 0.2-1% of photoacid generator, 0.01-0.2% of alkaline additive, 0.01-0.15% of leveling agent, and the balance is solvent.

8. The photoresist composition according to claim 7, characterized in that: The photoacid generator is at least one of diphenyliodonium trifluoromethanesulfonate, diphenyliodonium camphorsulfonate, diphenyliodonium perfluoro-1-butanesulfonate, diphenyliodonium perfluorooctanesulfonate, triphenylsulfonium trifluoromethanesulfonate, triphenylsulfonium camphorsulfonate, triphenylsulfonium perfluoro-1-butanesulfonate, and triphenylsulfonium perfluorooctanesulfonate; Preferably, the alkaline additive is at least one of tetrabutylammonium hydroxide, tetrabutylammonium acetate, tri-n-octylamine, 2,6-diisopropylamine, and diethanolamine; Preferably, the solvent is at least one of propylene glycol methyl ether acetate, ethyl lactate, 2-heptanone, ethylene glycol monomethyl ether acetate, and cyclohexanone.

9. A method for preparing a photoresist composition as claimed in claim 7 or 8, characterized in that: The steps include: S1. Add nano-silicon dioxide, carboxyl-terminated polyamidoamine and polyvinyl pyrrolidone to water for ultrasonic treatment for 1-2 hours, perform hydrothermal reaction at 200-230° C. for 2-6 hours, and the reaction pressure is 0.8-1 MPa. Then, the mixture is cooled to room temperature, centrifuged, washed, vacuum dried and crushed to obtain grafted titanium dioxide. S2. Add grafted titanium dioxide to water and stir evenly, add a photoacid generator thereto, ultrasonically treat for 1-2 hours, spray dry, add the 3,4-dihydroxystyrene polymer as described in claim 1 or 2, 3-hydroxy-1-adamantyl methacrylate, alkaline additive, and leveling agent, mix evenly, and add a solvent and mix evenly.

10. A method for using the photoresist composition according to claim 7 or 8, characterized in that: The method comprises the following steps: spin coating the photoresist composition as claimed in claim 7 or 8 on a silicon wafer, and sequentially performing pre-baking, exposure, post-baking and development to obtain a photolithographic pattern; The pre-baking temperature is 70-120°C and the exposure energy is 5-70mJ / cm 2 , post-baking temperature is 90-150℃; developing time is 30-130s.

Citation Information

Patent Citations

  • Acrylate copolymer and 248nm photoresist composition made thereof

    CN105566552A

  • Preparation method of silk-screen printing photo-sensitive adhesive

    CN108563100A

  • Heterocyclic polyfunctional photoinduced acid production agent, preparation method thereof and prepared chemical amplification photoresist

    CN110231754A

  • Photoresist composition

    CN110441989A

  • Easy-to-adhere and easy-to-remove photoresist

    CN112650022A